Exploring undergraduate hospitality student attitudes about online learning - Sparrow, Robert (Kansas State University, 2012)
Distance programs in higher education have become commonplace in the United States because of developments in technology. Despite these advancements, hospitality programs have been reluctant to create fully online offerings for undergraduate students. This study wanted to focus on understanding the attitudes of undergraduate hospitality students about online learning. Specifically, the objectives of this study were to determine the attitudes of hospitality students about online learning, to analyze which technologies they have used during their academic careers, and to analyze which technologies are perceived as most useful to facilitate learning. Focus groups were conducted with a select group of students to better understand their attitudes and experiences with online learning and learning technologies. An online survey was distributed to undergraduate hospitality management students at five Midwestern universities. Means and standard deviations were used to measure overall student attitudes about online learning and to measure ratings of effectiveness and past use of selected technologies for online learning. An analysis of variance (ANOVA) was used to determine the relationships between educational levels of students and perceptions of online technologies, as well as the relationship between experience with online courses and attitudes towards online learning. A t-test was used to determine if a relationship existed between gender and attitudes towards online learning. Results from this study revealed that respondents preferred to use more familiar technologies such as slideshow presentations and email for online learning. Students reported that they would miss the interaction with their professors if they took an online course and would receive less help. Females and males differed in their attitudes about online learning. Results from this study will assist hospitality curriculum developers to better understand the attitudes and needs of undergraduate hospitality management students in the online learning environment.
Keywords: Distance education; Online learning; Hospitality; Undergraduate students; Attitudes; Technologies; Social Sciences Education (0534)